Less grown apple varietes in juice production, and the influence of polyphenols and added ascorbic acid on the juice quality - Kuusi, Taina; Pajunen, Esko (Agricultural and Food Science, 1971)
Three apple varieties, Atlas, Erstaa, and Dolgo, were studied for their suitability for juice production and for the effect of polyphenols and added ascorbic acid on the juice quality. The Atlas and Erstaa varieties were found to be very suitable as raw material for apple juice production. The juices of Atlas were best in quality but they were sensitive to browning while Erstaa juices were not. The juices of Dolgo were considered too tart, but with an exceptionally interesting flavour. Dolgo juices could probably be used in mixtures together with sweeter apple varieties. Ascorbic acid could be used to prevent browning or to stop it to the desired degree and to stabilize the colour of the juice. The second alternative was found to be better because light brownish apple juices are generally preferred. The browning of apple juice was influenced not only by the polyphenolase activity and the polyphenol concentration but also by the type of phenolic compounds. In this respect proanthocyanidins and flavanols were most significant.